The pedagogical practices in an agricultural family school: a case study of Mathematics teaching from the perspective of Alternation Pedagogy (Research, Society and Development, 2020)
With the objective of observing the teaching-learning process in mathematics, as well as analyzing the perceptions of the education professionals of the Escola Família Agrícola (EFA) Normília Cunha dos Santos, a study was carried out that proposed to accompany the educational process from the perspective of pedagogy alternation. For this, a research was conducted in 2 stages: In the first stage, interviews were carried out with the education professionals responsible for the regular course of elementary education at the institution, where the data of the interviews were tabulated in categories and correlated to the themes identified by the authors of this study. In the second stage, a participant observation was conducted, in a supervised internship format, in the mathematics classes. Diagnostic activities and field classes were observed in order to meet the peculiarities of the alternation pedagogy regime. Through the interviews, a strong link between families and the community with the EFA could be inferred. The supervised internship at a school under the alternation pedagogy regime was also suggested as a possibility for understanding the best pedagogical praxis for rural education.